2002
DOI: 10.1007/s005300100047
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive video multicast scheme for varying workloads

Abstract: Periodic broadcast and scheduled multicast have been shown to be very effective in reducing the demand on server bandwidth. While periodic broadcast is better for popular videos, scheduled multicast is more suitable for less popular ones. Work has also been done to show that a hybrid of these techniques offer the best performance. Existing hybrid schemes, however, assume that the characteristic of the workload does not change with time. This assumption is not true for many applications, such as movie on demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The total communication load on the server for this set of clients is relative to maximum number of levels D /t w . This arrangement has the advantage that the server can detect LR problems quickly and is more reliable than any other scheme with message hopping from LR to LR until the server is reached [4], [15], [16]. After all, LRs are clients that can withdraw at any moment without notice.…”
Section: Figure 1 Hierarchy Under Lempmentioning
confidence: 99%
See 1 more Smart Citation
“…The total communication load on the server for this set of clients is relative to maximum number of levels D /t w . This arrangement has the advantage that the server can detect LR problems quickly and is more reliable than any other scheme with message hopping from LR to LR until the server is reached [4], [15], [16]. After all, LRs are clients that can withdraw at any moment without notice.…”
Section: Figure 1 Hierarchy Under Lempmentioning
confidence: 99%
“…This is not a novel approach [4], [9], [15], 16], but the organization of the underlying access control mechanism is, since we propose a semihierarchical overlay, against the tree-like arrangements proposed by other researchers (e.g., [16]). We also propose a different mechanism for the join and departure of clients, with emphasis on fault-tolerance and self-recovery and the reduction of control overhead and simultaneous server channels.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that a hybrid solution that combines both on-demand multicast and periodic broadcast offer the best performance [40]. The adaptive hybrid approach periodically measures the popularity of each video based on the distribution of recent service requests [40]. Popular videos are periodically broadcast using skyscraper broadcasting, and less requested videos are serviced using batching.…”
Section: Hybrid Broadcast Schemesmentioning
confidence: 99%
“…However, in general, these techniques are not applicable to less popular videos or a varying video access pattern. It was shown that a hybrid solution that combines both on-demand multicast and periodic broadcast offer the best performance [40]. The adaptive hybrid approach periodically measures the popularity of each video based on the distribution of recent service requests [40].…”
Section: Hybrid Broadcast Schemesmentioning
confidence: 99%